C/SiC composite coatings with ultra-high thermal emissivity. (3rd April 2021) - Yi, J.; Huang, J. P.; Song, G. P.; He, X. D.; Wang, B.; Jiang, N.
ABSTRACT: C/SiC gradient composite coatings with ultra-high emissivity have been deposited at 900°C on 316L stainless steel (SS) substrates using electron beam-physical vapour deposition (EB-PVD) by directly evaporating the raw powder of α-Sick The structural properties of the coating were investigated in detail. The results showed that the coating was mainly composed of C and nanocrystalline SiC. Its surface appeared to be dense and rough. Moreover, the thickness of the coating was about 0.7 μm, and good adhesional properties (no delamination) were found at the interface between the coating and the steel substrate. In addition, the thermal emissivity of the coating was analysed by FTIR spectroscopy. The result demonstrated that the coating had an ultra-high thermal emissivity.